Occurrence of Antibodies against Herpesvirus and Arteritis Virus in Equines from the State of Rio Grande do Norte, Brazil - Lopes Rocha, Leandro Lamartine; Diniz, Diogo Diógenes Medeiros; Souza de Jesus, Taile Katiele; Pinheiro Júnior, José Wilton; Villalobos, Eliana Monteforte Cassaro; Hunold Lara, Maria do Carmo Custodio de Souza; Rizzo, Huber (Acta Scientiae Veterinariae, 2020)
Background: Equine Herpesvirus type 1 (EHV-1) and Equine Arteritis Virus (EAV) have a high capacity for dissemination, causing losses in horse breeding due to reproductive, respiratory and neurological problems. In the State of Rio Grande do Norte there is only one survey, in the municipality of Mossoró, about these diseases. The purpose of this study was therefore to determine the prevalence and assess the risk factors associated with EHV-1 and EAV infections in unvaccinated horses raised in the mesoregions of East and West Potiguar in the State of Rio Grande do Norte, Brazil. Materials, Methods & Results: Between August 2018 and February 2019, blood samples were collected from equines on farms located in sixteen municipalities in the mesoregions of East and West Potiguar for the serological diagnosis of EAV (809 samples from 90 farms) and of EHV (778 samples from 88 farms), being that, only municipalities that had at least five hundred equines were included in the study. An investigative epidemiological questionnaire was applied to each property visited, containing questions related to the breeder, property, animal and the sanitary, reproductive and nutritional management. A logistic regression was performed to assess the risk factors associated with EVH, considering the serological test (positive or negative) as the dependent variable. EAV and EVH antibodies were detected through the serum virus neutralization assay. No evidence was found of EAV [0% (0/809)], but EHV showed a prevalence rate of 32% (249/778), with 80.6% (71/88) of the farms having at least one animal that tested positive, and EHV was present in all the municipalities covered in this study. The risk factors identified were: animals raised in East Potiguar (OR = 1.36, CI 95%: 1.01-1.85, P = 0.041), extensive livestock farming system (OR = 1.79, CI 95%: 1.10-2.91, P = 0.041), working animals (OR = 3.63, IC 95%: 1.91-6.91, P = 0.000), unclean facilities (OR = 2.32, CI 95%: 1.27-4.33, P = 0.006), and non-disinfected facilities (OR = 1.83, CI 95%: 1.15-2.91, P = 0.009). Discussion: The absence of horses seropositive for EAV confirms the findings reported for 132 cattle herding horses in the municipality of Mossoró, State of Rio Grande do Norte, Brazil, and by other national surveys that report zero or low occurrence rates. EAV is therefore considered an exotic disease that has not yet been diagnosed nor its etiological agent isolated in this country. EHV was found to be distributed in the two mesoregions, indicating a higher occurrence among working horses raised in the extensive livestock farming system on these farms, which were more physically fatigued and liable to be immunosuppressed, making them prone to infection, especially when left to graze in contact with other animals, although sports horses have also been found to be at high risk of becoming infected. The risk factor analysis also indicated the importance of hygiene and disinfection of livestock premises, where other biosafety measures such as quarantine and vaccination are likely not taken, and animals circulate unrestrictedly, facilitating the dissemination of the virus. Studies are therefore needed to shed light on the real situation of the presence of EAV throughout Brazil’s territory. On the other hand, EHV is widely disseminated throughout the state, and the risk factors for this disease not only underscore the importance of proper sanitary management for control of the disease but also serve as a warning to authorities and animal health professionals.